Terrorism risks in rural and frontier America. - Stamm, B.H (IEEE Engineering in medicine and biology magazine)
Policy for the safety of the United States must include an awareness of the importance of rural and frontier areas to urban areas. Water, power, and food are not available in sufficient amounts to support urban areas and are routinely shipped in from rural areas. National plans should address the increased costs of operating in rural areas and the increased burdens placed on most health and safety workers who work longer hours and take fewer days off. Other factors are also important, such as the status of regional hospitals (e.g. critical access, secondary, tertiary) and the type of Emergency Medical Service (volunteer versus paid), and the availability of HAZMAT teams and decontamination units. Regional infrastructure plays a part. It can include access to public transportation, highway systems, and the telecommunications network, as well as basic climate and geographical considerations, which includes proximity to a Metropolitan Statistical Area (MSA) that may provide resources for responding to disasters and terrorist attacks. Finally, it is important to take into consideration the base population, its median income, and the region's status as a health professions shortage area or otherwise medically underserved area.